IMPEDANCE CIRCUIT IDENTIFICATION THROUGH EVOLUTIONARY ALGORITHMS - Janeiro, Fernando M. (2012)
Impedance circuit identification through spectroscopy is used to characterize sensors. When the circuit topology is known, genetic algorithms can be used to obtain the circuit component values. Gene expression programming can be used to search for an adequate circuit topology. In this paper, an improved version of the impedance circuit identification based on gene expression programming and hybrid genetic algorithm is presented. Numerical results based on a real sensor are presented.